How to be happy with a Chatbot state machine. (Manning Publications, 2022)
The authors of the book "Natural Language Processing in Action, Second Edition'' work on some nessvec word embeddings for intent recognition and try to fix a bug in 'qary's' intent recognition logic. Also, they have built "therapy" skills for the `qary` virtual assistant (chatbot), which are based on the book "The Feeling Good Handbook" by David Burns.